2013
DOI: 10.1007/s10549-013-2416-2
|View full text |Cite
|
Sign up to set email alerts
|

PAM50 proliferation score as a predictor of weekly paclitaxel benefit in breast cancer

Abstract: To identify a group of patients who might benefit from the addition of weekly paclitaxel to conventional anthracycline-containing chemotherapy as adjuvant therapy of node-positive operable breast cancer. The predictive value of PAM50 subtypes and the 11-gene proliferation score contained within the PAM50 assay were evaluated in 820 patients from the GEICAM/9906 randomized phase III trial comparing adjuvant FEC to FEC followed by weekly paclitaxel (FEC-P). Multivariable Cox regression analyses of the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 42 publications
5
64
1
1
Order By: Relevance
“…Together, tumors collected across the three trials formed a combined cohort of 1,690 cases with formalin-fixed paraffin embedded tumor samples with intrinsic subtyping, and 1,557 of these cases had quantitative ER, PR, and HER2 centrally reviewed in each trial. Previous analyses found no statistically significant differences in clinicopathological characteristics or outcomes between subtyped trial subsets and the overall trial cohorts [19][20][21]. All biomarker studies were approved by the institutional research ethics board of the University of North Carolina at Chapel Hill.…”
Section: Study Populationsmentioning
confidence: 99%
“…Together, tumors collected across the three trials formed a combined cohort of 1,690 cases with formalin-fixed paraffin embedded tumor samples with intrinsic subtyping, and 1,557 of these cases had quantitative ER, PR, and HER2 centrally reviewed in each trial. Previous analyses found no statistically significant differences in clinicopathological characteristics or outcomes between subtyped trial subsets and the overall trial cohorts [19][20][21]. All biomarker studies were approved by the institutional research ethics board of the University of North Carolina at Chapel Hill.…”
Section: Study Populationsmentioning
confidence: 99%
“…Additionally, Prosigna ROR scores have been shown to be predictive of chemotherapy response. 102 Three studies have explored the ability of PAM50 to predict outcome in trials comparing two BACKGROUND NIHR Journals Library www.journalslibrary.nihr.ac.uk chemotherapy regimens, two of which were conducted in early breast cancer 103,104 and one in advanced disease. 105 None of the three studies selected patients by receptor expression, so the numbers of patients with luminal disease analysed was comparatively small.…”
Section: Pam50mentioning
confidence: 99%
“…One of the adjuvant studies compared an anthracycline containing regimen with CMF with an overall positive result. 103 The second adjuvant study, which was also positive, showed that patients with luminal A breast cancers appeared to benefit from paclitaxel treatment, unlike those with higher-risk subtypes, 104 which is a counterintuitive finding. In the study conducted in advanced disease, 105 which showed no overall benefit for the addition of gemcitabine to docetaxel, there appeared to be a significant benefit for patients with luminal B versus luminal A disease, which was lost in multivariate analysis.…”
Section: Pam50mentioning
confidence: 99%
“…In the United States, Prosigna ROR score was cleared by FDA in 2013 as a continuous predictor of distant recurrence in stage I node-negative and stage II node-negative and node-positive (1-3 nodes) postmenopausal HR þ breast cancer patients. Although there have been studies demonstrating the effectiveness of PAM50 and intrinsic subtyping in predicting outcome to (neo)adjuvant treatment (9,12,13), the chemopredictive value of Prosigna ROR score and intrinsic subtyping based on the Prosigna test has remained uncharacterized. In order to evaluate the performance of next-generation genomic tests for the purposes of guiding treatment prior to surgery, the following criteria can be used to lay the foundation for their clinical adoption: First, it is necessary to demonstrate the analytical validity of the testing platform with the associated tissue type.…”
Section: Introductionmentioning
confidence: 99%